Paradigm Space of Modern Higher Education in Ukraine - Viktoriya Zhelanova (Journal of Vasyl Stefanyk Precarpathian National University, 2020)
The article analyzes the paradigm space of higher education in Ukraine. It is proved that the modern education paradigm has a synthetic character, is based on the polyparadigmality principles and is a synthesis of personally oriented ideas, semantic and cognitive paradigms of education. Their nature and characteristics are considered. The units of analysis selected certain components of the paradigm, namely: mission, goals, objectives, guiding values, content of education, basic didactic tools, teacher-student relationships, criteria, functions. It is proved that the situation of confrontation and contradiction of personally oriented, semantic and cognitive paradigms of education is unacceptable, since each of them has its positives and limitations. It was found that cognitive education provides significant potential for intellectual development of the individual, it is its apparent positive. Proved that the cognitive limitations of education lies in its normative and purely social utility, which not related to the unique personality implementation, which is a passive “object” of teacher pedagogical influence; informative cognitive priority led to its content and disciplinary overload, is a serious problem of modern education in higher education institutions. Proved that priority is individually oriented paradigm associated with the formation of free, individual initiative as the “subject” of his life and this education paradigm is reflexive oriented because its values are leading self-awareness, self-development and personal fulfilment future specialist. However, objective knowledge is sometimes overlooked, and this is a certain difficulty of personally oriented education. It is found out that the benefits of the education semantic paradigm are related to the value-semantic attitude formation towards future professional activity, with updating of personal semantic experience; with semantic choice, with development of future specialist semantic potential. The reflexive nature of the personally oriented, semantic and cognitive paradigms of education is substantiated, and it is proved that the modern paradigm of higher education space will constitute a polyparadigmatic synthesis of their ideas accumulated in the education reflexive paradigm. The polyparadigmality essence is revealed as a research methodology, which is a conceptual synthesis of several existing educational paradigms.